GOLD LOANS AT ISLAMIC BANK AMANAH SYARIAH BASED ON THE PERSPECTIVE OF ISLAMIC ECONOMIC LAW - Yana Ilham; Mahdalena Nasrun (JURISTA: Jurnal Hukum dan Keadilan, 2022)
Institutions engaged in capital have their own system or method of channeling capital, such as the Amanah Syariah UPK which is an institution that manages activities to overcome and assist in the economic field, carried out independently in developing community welfare. Capital provided in the form of loans or debts with the object being gold. The focus of the problem in this study is how the consideration of UPK Amanah Syariah provides loans in the form of gold, how is the mechanism of gold loan practices at UPK Amanah Syariah Samatiga District, West Aceh Regency? and how the Islamic economic review of the management of profit sharing in gold loan practices at UPK Amanah Syariah. This research is a field research by conducting interviews and documentation, while the data analysis method is descriptive qualitative. This study concludes that first, the consideration of providing loans in the form of gold is based on the results of deliberations of several parties which resulted in a convention from conventional UPK to UPK Amanah Syariah to avoid usury. Second, the service set is 10% per year, lower than the previous 18%. The practice carried out at the time of ijab qabul uses a murabahah contract. Lending and returning according to the gold in the contract, or it can also be in the form of money worth the gold loaned.